Properties of Soil in Najaf Governorate - Alsaedi, Jamal K.; Hasan, Nada M.; Hassan, Raad G. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Eight soil samples were selected around Najaf governorate at depth levels 40-50 cm. X-Ray Fluorescence (XRF) was used to determine the concentrations of major and trace elements. Liner and mass attenuation coefï¬cient (Âµ, ÂµÏ) have been determined at gamma energies (662, 1172,1332) keV using NaI (Tl) detector. The range of linear attenuation coefficients for calculated samples were (0.553-1.163) cm-1, (0.122-0.178) cm-1 and (0.049-0.105) cm-1 at (662, 1172,1332) keV respectively. The range of mass attenuation coefficients obtained (0.39-0.76) cm2/gm, (0.087-0.117) cm2/gm and (0.0336-0.074) cm2/gm at (662, 1172,1332) keV respectively. The results showed that Fe content in the samples has a strong effect on the mass attenuation coefficient and this parameter is inversely proportional to the gamma energy.